The Influence of Online Customer Review, Promotions, and Product Quality on the Purchasing Decisions of Gen Z Consumers (Study on the Originote Skincare Products) - Adhalul Ade Laila; Rizky Eka Febriansah; Rita Ambarwati Sukomono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Gen Z is the main focus in skincare product marketing strategies. Online customer reviews, promotions, and product quality are important factors in Gen Z's purchasing decisions. This study aims to determine the influence of online customer reviews, promotions, and product quality on consumer purchasing decisions. This study uses quantitative methods. The sampling method uses non-probability sampling. The population in this study is Gen Z. Data collection techniques use primary and secondary data. Primary data is obtained from the results of distributing questionnaires via Google Forms, and secondary data is obtained from books, journals, and articles. Data analysis techniques use Partial Least Square (PLS) version 4.0. The results of this study indicate that (1) Online Customer Reviews have a positive and significant effect on purchasing decisions. (2) Promotion has a positive and significant effect on purchasing decisions. (3) Product Quality has a positive and significant effect on purchasing decisions.